Reading Faces and Bodies: Behavioral and Neural Processes Underlying the Understanding of,and Interaction with, Others - Paola Ricciardelli (Frontiers Research Topics, 2017)
The aim of this Research Topic was to offer an interdisciplinary forum for researchers interested in the interplay of face, eye gaze, and body perception in the understanding of others, with an emphasis on behavioural and neural processing. The papers included in this topic come from cognitive, neuroscience and social psychology perspectives and shed new light on how facial and body cues interact with each other and with social, ecological and contextual factors (such as for example social identification and group membership) to form a unified representation that can guide our perceptions and responses to other people. Altogether, they provide an up-to-date picture of advances in this fascinating research field.